67 Echocardiography vs. computed tomography and cardiac magnetic resonance for the detection of left heart thrombosis: a systematic review and meta-analysis. (17th December 2020) - Aimo, Alberto; Ntritsos, Georgios; Masci, Pier-Giorgio; Figliozzi, Stefano; Klettas, Dimitrios; Stamatelopoulos, Kimon; Delialis, Dimitrios; Emdin, Michele; Georgiopoulos, Georgios
Abstract: Aims: Accurate and reproducible diagnostic techniques are essential to detect left-sided cardiac thrombi (either in the left ventricle [LV] or in the left atrial appendage [LAA]) and to guide the onset and duration of antithrombotic treatment while minimizing the risk for thromboembolic and hemorrhagic events. Methods and results: We conducted a systematic review and meta-analysis aiming to compare the diagnostic performance of transthoracic echocardiography (TTE) vs. cardiac magnetic resonance (CMR) for the detection of LV thrombi, and transesophageal echocardiography (TEE) vs. computed tomography (CT) for the detection of LAA thrombi. Six studies were included in the first meta-analysis. Pooled sensitivity and specificity values were 62% (95% confidence interval [CI], 37-81%) and 97% (95% CI, 94-99%). The shape of the hierarchical summary receiver operating characteristic (HSROC) curve and the area under the curve (AUC) of 0.96 suggested a high accuracy. Ten studies were included in the meta-analysis of the diagnostic accuracy of CT vs. TEE. The pooled values of sensitivity and specificity were 97% (95% CI, 77-100%) and 94% (95% CI, 87-98%). The pooled DOR was 500 (95% CI, 52-4810), and the pooled LR+ and LR- values were 17% (95% CI, 7-40%) and 3% (95% CI, 0-28%). The shape of the HSROC curve and the 0.99 AUC suggested a high accuracy of CT vs. TEE. Conclusion: TTE is a valid alternative to DE-CMR for the identification of LV thrombi, and CT has a good accuracy compared to TEE for the detection of LAA thrombosis.